Bioactive compounds present in the Mediterranean sofrito - Vallverdú-Queralt, Anna; Alvarenga, José Fernando Rinaldi de [UNESP]; Estruch, Ramon; Lamuela-Raventos, Rosa M. (Elsevier, 2013)
Sofrito is a key component of the Mediterranean diet, a diet that is strongly associated with a reduced risk of cardiovascular events. In this study, different Mediterranean sofritos were analysed for their content of polyphenols and carotenoids after a suitable work-up extraction procedure using liquid chromatography/electrospray ionisation-linear ion trap quadrupole-Orbitrap-mass spectrometry (LC/ESI-LTQ-Orbitrap- MS) and liquid chromatography/electrospray ionisation tandem triple quadrupole mass spectrometry (LC/ESI-MS-MS). In this way, 40 polyphenols (simple phenolic and hydroxycinnamoylquinic acids, and flavone, flavonol and dihydrochalcone derivatives) were identified with very good mass accuracy (<2 mDa), and confirmed by accurate mass measurements in MS and MS2 modes. The high-resolution MS analyses revealed the presence of polyphenols never previously reported in Mediterranean sofrito. The quantification levels of phenolic and carotenoid compounds led to the distinction of features among different Mediterranean sofritos according to the type of vegetables (garlic and onions) or olive oil added for their production. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Carotenoids; HPLC-LTQ-Orbitrap-MS; HPLC-MS-MS; Polyphenols; Sofrito